1988
DOI: 10.1021/ja00228a054
|View full text |Cite
|
Sign up to set email alerts
|

Reversible metal-metal bond cleavage accompanied by the facile reversible addition of hydrogen to a Ru3 cluster. Synthesis and x-ray structures of Ru3(CO)8(.mu.-H)2(.mu.-tert-Bu2P)2 and Ru3(CO)8(.mu.-H)2(H)2(.mu.-tert-Bu2P)2

Abstract: The reversible formation and cleavage of a metal-metal bond is a key reaction in dinuclear and cluster chemistry.1 A few cases have been reported in which such a process is accompanied by the reversible addition of two electron donors such as CO or PR,.1 However, to our knowledge there have, so far, been no well characterized examples of the complete cleavage of a metal-metal bond accompanied by the reversible addition of H2 under mild conditions. There are relatively few examples of the reversible addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…The new cluster (μ-H) 2 Ru 3 (CO) 8 (μ-PCyc 2 ) 2 was prepared by the procedure used for the di- tert -butylphosphido analog. The spectroscopic data are entirely analogous to those for (μ-H) 2 Ru 3 (CO) 8 (μ-PR 2 ) 2 , R = Ph 14 and t -Bu . The clusters (μ-H) 2 Ru 3 (CO) 8 (μ-PPh 2 ) 2 and (μ-H) 2 Ru 3 (CO) 8 (μ-PCyc 2 ) 2 do not react with hydrogen under the conditions examined.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…The new cluster (μ-H) 2 Ru 3 (CO) 8 (μ-PCyc 2 ) 2 was prepared by the procedure used for the di- tert -butylphosphido analog. The spectroscopic data are entirely analogous to those for (μ-H) 2 Ru 3 (CO) 8 (μ-PR 2 ) 2 , R = Ph 14 and t -Bu . The clusters (μ-H) 2 Ru 3 (CO) 8 (μ-PPh 2 ) 2 and (μ-H) 2 Ru 3 (CO) 8 (μ-PCyc 2 ) 2 do not react with hydrogen under the conditions examined.…”
Section: Resultssupporting
confidence: 59%
“…In 1988 Jones et al described the reaction of hydrogen with (μ-H) 2 Ru 3 (CO) 8 (μ-P( t -Bu) 2 ) 2 , in which addition occurs quantitatively and reversibly across an unbridged metal−metal bond, producing (μ-H) 2 Ru 3 (H) 2 (CO) 8 (μ-P( t -Bu) 2 ) 2 (Figure ) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] H 2 addition to the saturated 48-electron triangular cluster (µ-H) 2 Ru 3 (CO) 8 (µ-PtBu 2 ) 2 (16) results in the opening up of the cluster to form a linear, also electron-precise, Ru 3 trimetallic species (µ-H)H 2 Ru 3 (CO) 8 (µ-PtBu 2 ) 2 (17), with no overall loss of CO. Purging a solution with N 2 reforms the starting cluster 16, although in the solid state the cluster is stable to H 2 loss. [42] Detailed kinetic studies demonstrated that the mechanism involves CO loss (thus forming an unsaturated cluster) that precedes H 2 addition to a singlemetal centre with concomitant breaking of a Ru-Ru bond. Addition of CO affords the product that has made a net gain of H 2 .…”
Section: Equilibrium Reversible (H 2 Is Lost Upon Removal Of the H 2 mentioning
confidence: 99%
“…Other authors reported the same reaction behavior during the reaction of the ruthenium carbonyl with the bulky phosphane P t Bu 2 H (molar ratio 1:2) in refluxing dibutyl ether resulting in [Ru 3 (μ‐H) 2 (μ‐P t Bu 2 ) 2 (CO) 8 ] . 3 crystallized from CH 2 Cl 2 /diethyl ether at room temperature as yellow crystals belonging to the monoclinic space group P 2 1 / n with four molecules in the unit cell.…”
Section: Resultsmentioning
confidence: 60%